Analisis Dampak Pendidikan Dan Akses Keuangan Terhadap Penanggulangan Kemiskinan - Muhammad Jiyad Naufal; Stefanus Surbakti; Rahulsep Lukas Tampubolon; Robin Silalahi; Wiwin Zakiah (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
Poverty is a serious challenge that involves various aspects of human life. Poverty is often a major obstacle to sustainable development and equitable distribution of wealth. This study aims to investigate and analyze the impact of education and access to finance on poverty reduction. The research method utilizes a desk study analysis, also involving secondary data analysis from various sources, including government data and related studies. With this approach, it is expected that this research can provide a comprehensive picture of the impact of education and access to finance on poverty reduction. The result of the research is that this study confirms the importance of strategic integration between education and financial access in poverty reduction efforts.